The history of Coast Salish “woolly dogs” revealed by ancient genomics and Indigenous Knowledge - Lin, AT; Hammond-Kaarremaa, L; Liu, H-L; Stantis, C; McKechnie, I; Pavel, M; Pavel, SSM; Wyss, SSÁ; Sparrow, DQ; Carr, K; Aninta, SG; Perri, A; et al. (American Association for the Advancement of Science, 2023)
Ancestral Coast Salish societies in the Pacific Northwest kept long-haired "woolly dogs" that were bred and cared for over millennia. However, the dog wool-weaving tradition declined during the 19th century, and the population was lost. In this study, we analyzed genomic and isotopic data from a preserved woolly dog pelt from "Mutton," collected in 1859. Mutton is the only known example of an Indigenous North American dog with dominant precolonial ancestry postdating the onset of settler colonialism. We identified candidate genetic variants potentially linked with their distinct woolly phenotype. We integrated these data with interviews from Coast Salish Elders, Knowledge Keepers, and weavers about shared traditional knowledge and memories surrounding woolly dogs, their importance within Coast Salish societies, and how colonial policies led directly to their disappearance.